Protective Effects of Baicalin on Experimental Myocardial Infarction in Rats - Longfei Wang (Revista Brasileira de Cirurgia Cardiovascular/Brazilian Journal of Cardiovascular Surgery, 2018)
Objective: This study aimed to investigate the protective effects of baicalin on myocardial infarction in rats and explore the related mechanisms.Methods: Fifty Sprague Dawley rats were randomly divided into the control, model, and low-, medium- and high-dose baicalin groups. The latter 3 groups were intraperitoneally injected with baicalin, with a dose of 12.5, 25 and 50 mg/kg, respectively. Then, the myocardial infarction model was established. The hemodynamic of rats was tested, the serum lactate dehydrogenase (LDH), creatine kinase-MB (CK-MB), prostacyclin (PGI2) and thromboxane A2 (TXA2) were determined, the myocardial superoxide dismutase (SOD) and malondialdehyde (MDA) levels were detected, and the myocardial B-cell lymphoma-2 (Bcl-2) and Bcl-2 associated X (Bax) protein expressions were determined.Results: Compared with the model group, in the high-dose baicalin group the ST segment height and LVEDP were significantly decreased (P<0.05), the LVSP was significantly increased (P<0.05), the serum LDH, CK-MB and TXA2 levels were significantly decreased (P<0.05), the PGI2 level was significantly increased (P<0.05), the myocardial SOD level was significantly increased (P<0.05), and the myocardial MDA level was significantly decreased (P<0.05); the myocardial Bcl-2 protein level was significantly increased, and the Bax protein level was significantly decreased (P<0.05).Conclusion: Baicalin has protective effects on myocardial infarction in rats. The possible mechanisms may be related to its resistance to oxidative stress, and up-regulation of Bcl-2 protein expression and down-regulation of Bax protein expression in myocardial tissue.